One-step purification of 5-enolpyruvylshikimate-3-phosphate synthase enzyme from Mycobacterium tuberculosis - Oliveira, Jaim S.; Mendes, Maria A.; Palma, Mario Sergio [UNESP]; Basso, Luiz A.; Santos, Diógenes S. (Elsevier, 2003)
Currently, there are 8 million new cases and 2 million deaths annually from tuberculosis, and it is expected that a total of 225 million new cases and 79 million deaths will occur between 1998 and 2030. The reemergence of tuberculosis as a public health threat, the high susceptibility of HIV-infected persons, and the proliferation of multi-drug-resistant strains have created a need to develop new antimycobacterial agents. The existence of homologues to the shikimate pathway enzymes has been predicted by the determination of the genome sequence of Mycobacterium tuberculosis. We have previously reported the cloning and overexpression of M. tuberculosis aro A-encoded EPSP synthase in both soluble and active forms, without IPTG induction. Here, we describe the purification of M. tuberculosis EPSP synthase (mtEPSPS) expressed in Escherichia coli BL21(DE3) host cells. Purification of mtEPSPS was achieved by a one-step purification protocol using an anion exchange column. The activity of the homogeneous enzyme was measured by a coupled assay using purified shikimate kinase and purine nucleoside phosphorylase proteins. A total of 53 mg of homogeneous enzyme could be obtained from 1 L of LB cell culture, with a specific activity value of approximately 18 U mg-1. The results presented here provide protein in quantities necessary for structural and kinetic studies, which are currently underway in our laboratory. © 2002 Elsevier Science (USA). All rights reserved.
Keywords: 3-Phosphoshikimate 1-Carboxyvinyltransferase; Alkyl and Aryl Transferases; Chromatography, Ion Exchange; Escherichia coli; Gene Expression Regulation, Enzymologic; Mass Spectrometry; Mycobacterium tuberculosis; Phosphotransferases (Alcohol Group Acceptor); Purine-Nucleoside Phosphorylase; Recombinant Proteins; Mycobacterium